Crucial competencies for crisis management: the importance of middle leaders’ conceptual skills in navigating turbulent times - Mohd Ariffin, Juliza Adira; Md Rami, Ahmad Aizuddin; Muhamad Nasharudin, Nurfazreen Aina; Zaremohzzabieh, Zeinab (Routledge, 2024)
In the contemporary landscape characterized by volatility, uncertainty, complexity, and ambiguity (VUCA), crises can arise, placing organizations at risk. To prevent such failures, organizations must have capable leaders who possess the necessary crisis management competencies to handle such situations. Effective crisis management involves four crucial competencies: improvisation skills, analytical thinking skills, strategic planning skills, and change management skills. This study purposes to evaluate the essential leadership competencies required for effective crisis management, with a specific focus on conceptual competencies among middle leaders in Malaysia’s Ministry of Education (MOE). Utilizing the Fuzzy Delphi Method (FDM), this research seeks to obtain expert consensus on the most critical competencies required for effective crisis management. An instrument containing a list of conceptual competencies was presented to a diverse panel of 15 experts, including those with expertise in crisis management and education. The four elements tested surpassed the required conditions set in FDM. The defuzzification process also rearranged all the elements. In conclusion, this study successfully identified four crisis management competencies that are crucial for middle leaders in educational organizations. The study’s findings have benefits for theoretical evolution, policy development for organizational education, and practice, especially for middle leaders in educational organizations towards sustainable education.